Toxicity of straight-chain fatty acids to leaf-cutting ants Atta sexdens rubropilosa (Hymenoptera: Formicidae) and the symbiotic fungus Leucoagaricus gongylophorus - Peñaflor, M. Fernanda G. V. [UNESP]; Victor, Sandra R. [UNESP]; Bueno, Odair C. [UNESP]; Hebling, M. José A. [UNESP]; Pagnocca, Fernando C. [UNESP]; Leite, Ana C.; Fernandes, João B.; Vieira, Paulo C.; Da Silva, M. Fátima G. F. (My University, 2006)
This work determined toxicity and attractiveness of straight-chain fatty acids (C 5 to C 12) to Atta sexdens rubropilosa (Forel) workers. The effect to the symbiotic fungus, Leucoagaricus gongylophorus (Singer) Möller, was also tested with the fatty acids C 6 to C 12. A strong mortality of leaf-cutting ants that were fed with an artificial diet containing fatty acids C to C at concentrations above 1.0 mg.ml -1 was observed. Rice flakes impregnated with solutions of these fatty acids were repellent to leaf-cutting ants. Contact experiments showed that treatments with C 6 and C 7 at concentration of 100 mg.ml -1 significantly reduced the survival rate of leaf-cutting ants. The fatty acids C 8 to C 11 were toxic to leaf-cutting ants when topically tested at concentration of 200 mg.ml -1. In relation to the fungus' bioassays, the fatty acids C 6 to C 12 at concentration of 0.1 mg.ml -1 inhibited 100% of the fungal development. Although when the concentration was reduced by half no inhibition effects were observed. The results showed that straight-chain fatty acids have desirable properties for controlling leaf-cutting ants since they directly interfere with both organisms of the symbiotic relationship. The potential of fatty acids as well as ways to control leaf-cutting ants with these compounds are discussed in this article.
Keywords: Atta sexdens rubropilosa; Control; Fatty acids; Fungistatic; Leucoagaricus gongylophorus; Repellent; Toxicity; Atta; Formicidae; Fungi; Hymenoptera